Peran Artificial Intelligence dalam Pengembangan UMKM di Era Digital - Aysa, Imma Rokhmatul; Nurfitriani, Ika; Husna, Murni (Universitas Islam Tribakti Lirboyo Kediri, 2024)
MSMEs which are an important pillar of economic development to be able to make a greater contribution to the economy should be able to develop their business with the help of Artificial Intelligence / AI, but the current conditions in the field are still many MSME players who have not adopted AI for product development and promotion due to lack of HR knowledge. From these problems, the researcher aims to examine the role of AI in the development of MSMEs with a focus on analyzing the role of AI in supporting several economic activities in MSMEs. Through an analytical descriptive approach, this research will explore how MSME players in various sectors use AI to improve efficiency, optimize decision making. The result of this research is that AI is currently having a big impact on the MSME sector, MSME players can gain deep insights into market trends, consumer behavior, and integrate effective and efficient business strategies. With AI they can innovate products and the media for promoting MSME products are also increasingly diverse through websites and e-commerce.